Protective effects of chronic mild stress during adolescence in the low-novelty responder rat. (2nd January 2016) - Rana, Samir; Nam, Hyungwoo; Glover, Matthew E.; Akil, Huda; Watson, Stanley J.; Clinton, Sarah M.; Kerman, Ilan A.
Abstract: Stress-elicited behavioral and physiologic responses vary widely across individuals and depend on a combination of environmental and genetic factors. Adolescence is an important developmental period when neural circuits that guide emotional behavior and stress reactivity are still maturing. A critical question is whether stress exposure elicits contrasting effects when it occurs during adolescence versus adulthood. We previously found that Sprague–Dawley rats selectively bred for low-behavioral response to novelty (bred Low Responders; bLRs) are particularly sensitive to chronic unpredictable mild stress (CMS) exposure in adulthood, which exacerbates their typically high levels of spontaneous depressive- and anxiety-like behavior. Given developmental processes known to occur during adolescence, we sought to determine whether the impact of CMS on bLR rats is equivalent when they are exposed to it during adolescence as compared with adulthood. Young bLR rats were either exposed to CMS or control condition from postnatal days 35–60. As adults, we found that CMS-exposed bLRs maintained high levels of sucrose preference and exhibited increased social exploration along with decreased immobility on the forced swim test compared with bLR controls. These data indicate a protective effect of CMS exposure during adolescence in bLR rats.